Metode Penanaman Nilai Agama dan Moral Pada Anak Usia Dini - Fitriani, Ana; Rukhiyati, Iit; listiani, Meri; Sumiyati, Sumiyati; Syamsiah, Syamsiah (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Instilling religious and moral values ​​in early childhood is an essential part of developing fundamental character, which will influence their behavior later in life. This article discusses various approaches used in education, including role-playing, habituation, storytelling, role-playing, and hands-on experiences in daily life. This study assesses the extent to which these techniques can influence children's moral and spiritual development using descriptive and analytical approaches. The discussion reveals that the effectiveness of these methods is greatly influenced by consistent educator behavior, family involvement, and a learning environment that supports the consistent application of values. Therefore, instilling religious and moral values ​​requires a comprehensively planned approach and evaluation to ensure that it does not become merely a routine but truly shapes children's character.